A promising antibiotic, synergistic and antibiofilm effects of Vernonia condensata Baker (Asteraceae) on Staphylococcus aureus. (October 2018) - da Silva, Jucélia Barbosa; de Bessa, Martha Eunice; Santos Mayorga, Oscar Alejandro; Andrade, Vívian Tomasco; da Costa, Ygor Ferreira Garcia; de Freitas Mendes, Renata; Pires Ferreira, Adriana Lúcia; Scio, Elita; Alves, Maria Silvana
Abstract: Vernonia condensata Baker is traditionally used to treat several inflammatory and infectious processes. So, this study evaluated the antibiotic, synergistic and antibiofilm effects, and the mode of action of ethyl acetate fraction from V. condensata leaves (Vc-EAF) against Staphylococcus aureus . Five S. aureus ATCC ® and five methicillin-resistant S. aureus (MRSA) routine strains were used to determine Minimal Inhibitory Concentration (MIC) and Minimal Bactericidal Concentration. The combinatory effect was evaluated by checkerboard and time kill methods; the mode of action through the bacterial cell viability and leakage of compounds absorbing at 280 nm; and the antibiofilm action by quantifying the percentage of adhesion inhibition. Vc-EAF was active against S. aureus (ATCC ® 6538 ™ ), (ATCC ® 25923 ™ ), (ATCC ® 29213 ™ ), (ATCC ® 33591 ™ ), (ATCC ® 33592 ™ ), MRSA 1485279, 1605677, 1664534, 1688441 and 1830466, with MIC of 625 μg/mL for ATCC ®, and 1250, 1250, >2500, 2500 and 2500 μg/mL for MRSA, in this order, with bacteriostatic effect for both ATCC ® and MRSA strains. Vc-EAF plus ampicillin revealed a total synergic effect on MRSA 1485279, and Vc-EAF combined with chloramphenicol, a partial synergic action against S. aureus (ATCC ® 29213 ™ ) and (ATCC ® 25923 ™ ). The time kill data agreed with checkerboard results, and the treated cells number was reduced with release of bacterial content. An expressive bacterial adhesion inhibition for S. aureus (ATCC ® 25923 ™ ) and MRSA 1485279 was detected. These results showed that V. condensata is a promising natural source of active substances against S. aureus, including multiresistant strains, interfering with their antibacterial growth and hampering their adhesion to surfaces. Graphical abstract: Highlights: Antibiotic effect of Vernonia condensata on Staphylococcus aureus was reported. Vc-EAF combined with ampicillin possess total synergic effect against S. aureus. Vc-EAF with chloramphenicol possess partial synergic effect against S. aureus. Vernonia condensata probably affects the bacterial membrane permeability. Vc-EAF showed an antibiofilm effect with S. aureus biofilm forming strains.